The Category of Politeness and Apology - PARONYAN, SHUSHANIK; TAMOYAN, NARE (Bulletin of Yerevan University B: Philology, 2021)
In the present article an attempt is made to highlight the peculiarities of the correlation between the category of politeness and apology in the process of human interaction. It is stated that politeness and apology are marked by structural, semantic and functional manifoldness and, furthermore, they are aimed at the creation, maintenance or restoration of harmony in human relations. The main aim of the article is to lead the reader to the idea that although politeness and apology have certain crossing points, they are relatively autonomous entities in the process of communication. This can be explained by the fact that not all acts of apology should be viewed from the standpoint of politeness, and politeness, in its turn, as a manifestation of discourse policy, is peculiar not only to the speech acts of apology but also to a range of other speech acts. Interesting observations are also made about the correlation between sincerity and politeness in communicative situations containing acts of apology.